2021
DOI: 10.1152/ajpgi.00114.2021
|View full text |Cite
|
Sign up to set email alerts
|

miR-128 participates in the pathogenesis of chronic constipation by regulating the p38α/M-CSF inflammatory signaling pathway

Abstract: Chronic constipation (CC) is a gastrointestinal disorder that adversely affects the quality of life. MicroRNAs are involved in the pathogenesis of functional gastrointestinal disorders. This study aims to investigate the molecular mechanism of microRNA-128 in CC. Here, we successfully constructed a murine model of CC based on morphine and rhubarb. The expression of stem cell factor (SCF) and neuron-specific enolase (NSE) were low in the models. Using miRNA array and bioinformatic analysis, we predicted and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…ere is evidence that miRNAs take part in the pathogenesis of STC [43][44][45]. e results of co-expression network analysis and RNA-seq analysis showed that co-expressed miRNA networks with specific genes and pathways are related to STC [46,47].…”
Section: Discussionmentioning
confidence: 98%
“…ere is evidence that miRNAs take part in the pathogenesis of STC [43][44][45]. e results of co-expression network analysis and RNA-seq analysis showed that co-expressed miRNA networks with specific genes and pathways are related to STC [46,47].…”
Section: Discussionmentioning
confidence: 98%
“…Pathways associated with SOCS1, SHIP1, C/EBP-β, and IL13Rα1 signaling cascades might regulate the development CASPR2 encephalitis but not LGI1 encephalitis. miR-128 was reported to participate in the inflammation pathogenesis by regulating the p38α/M-CSF inflammatory signaling pathway [ 54 ]. Thus, p38α/M-CSF inflammatory signaling pathway might fine-tune anti-LGI1- and anti-CASPR2-associated encephalitis.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs, such as miR-let-7f, miR-let-7e, and miR-200a-3p, were reported to be capable of decreasing the current density of NaV1.5 channel in colonic smooth muscle cells and thus increasing the contractile frequency and amplitude of smooth muscle strips via inhibiting the expression of target gene SCN5A ( 24 ). In an animal experiment, miR-128 was found to present significantly elevated expression in the colonic tissue of mice with functional constipation, which inhibited the p38α/M-CSF signaling pathway leading to impaired function of Cajal cells ( 33 ). The imbalance of intestinal microbiota caused by the disorders of miRNA and related regulatory networks is important for the pathogenesis of SCC.…”
Section: Discussionmentioning
confidence: 99%